2018
DOI: 10.31783/elsr.2018.417284
|View full text |Cite
|
Sign up to set email alerts
|

Application of principal component analysis for rice f5 families characterization and evaluation

Abstract: The type and level of genetic variance in one hundred and fourteen F5 families of rice obtained from six different crosses was estimated along with their seven parents using Mahalanobis D 2 -statistics by considering 10 characters. Mahalanobis D 2 analysis revealed considerable amount of diversity in the material. The genotypes were grouped into twelve clusters. Cluster IX constituted maximum number of genotypes (26). The genotypes falling in cluster VII had the maximum divergence, which was closely followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…In the fifth principal component, number of spikelets/panicle, flag leaf width, number of filled grains/panicle and biological yield is the greatest contributor to the observed variation. Similar kind of results were found by [35,36,37]. Based on PCA most of the important yield and yield attributing traits were present in PC5 (Table 10) and from first three PCs it was cleared that the days to Days to 50% flowering, Plant height and panicle length is high.…”
Section: Principle Component Analysissupporting
confidence: 80%
“…In the fifth principal component, number of spikelets/panicle, flag leaf width, number of filled grains/panicle and biological yield is the greatest contributor to the observed variation. Similar kind of results were found by [35,36,37]. Based on PCA most of the important yield and yield attributing traits were present in PC5 (Table 10) and from first three PCs it was cleared that the days to Days to 50% flowering, Plant height and panicle length is high.…”
Section: Principle Component Analysissupporting
confidence: 80%
“…Findings of PCA (Table 6) showed that first five PCs (Fig 1) recorded eigen values greater than one and contributed to 75.32 per cent of variability among the 32 mutant families in M 3 generation. In the previous studies Riaz et al (2018), Tejaswini et al (2018) found that first five PCs were explained the maximum variance of the total set. The PC 1 explained 23.87 per cent of total variation which was elucidated by all the quantitative traits with positive eigen vector whereas, panicle weight, panicle length and plant height were higher contributing traits to the total variation.…”
Section: Principal Component Analysismentioning
confidence: 87%
“…2 and Fig. 3) Evaluation of rice genotypes through PCA 3D scatter diagram was also carried out by Tejaswini et al (2018) and Ibrahim et al (2021).…”
Section: Sujan Acharjee Et Almentioning
confidence: 99%
“…According to Tejaswini et al (2018), the genotypes identified on the extremely positive side of both the X and Y axis were considered to be better genotypes against the contributing traits of PC 1 and PC 2, respectively, however, in the 3D (three dimensional) scattered diagram, it was considered an additional vertical Z-axis and in that case, the genotypes plotted higher along the Z-axis will also be considered as better performers against the contributing traits of PC 3. Under, irrigated condition, PC1 was loaded with high coefficient values ( irrespective of direction) of most of the grain yield-related traits, thus the genotypes reside towards the higher value or right side along with the PCA score I axis (X-axis) of the 3D scattered diagram ( Fig 2 .) may be considered as promising landraces as far as grain yield is concerned.…”
Section: Sujan Acharjee Et Almentioning
confidence: 99%